Fertilitas di Kabupaten Sleman Yogyakarta Tahun 2023: Demografi, Sosial dan Ekonomi - Aryati, Seri; Sukamdi, Sukamdi; Listyaningsih, Umi (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2025)
This paper examines fertility in Sleman Regency, Yogyakarta, with a focus on socio-demographic and economic factors. Sleman, a region of strategic significance within the Special Region of Yogyakarta, exhibits unique demographic characteristics that warrant further analysis, particularly in relation to fertility rates. The study highlights the impact of factors such as age at first marriage, ideal number of children, live births, education, employment, contraceptive use, and reasons for not using family planning. Utilizing secondary data from the 2023 Family Survey and Update conducted by BKKBN, the study finds that most residents prefer smaller families, with two children considered ideal. This paper also emphasizes the crucial role of access to healthcare services in shaping fertility patterns. The findings provide valuable insights into local demographic dynamics and offer guidance for policy development aimed at managing population growth and promoting sustainable development.